High performance liquid chromatography quality control - Mohammed El Amine, M.; E. Ghanjaoui, A.; Mandil, A.; Ait Sidi Mou, A.; Slimani, R. (International Journal of Advanced Chemistry, 2020)
This review gives a general overview of High Performance Liquid Chromatography (HPLC) Method for the detection, the separation and the quantification of the active compounds from the organics matrices. A brief description of the instrumentation and the method devel-opment is provided. The principles of HPLC including different separation modes and detection methods for the quantitative analysis are summarized. Finely, the validation procedures in real samples are also described.Â Â